Evaluasi Kesesuaian Lahan dan Kelayakan Ekonomi Untuk Pengembangan Tanaman Jahe Merah (Zingiber offcinale var. Rubrum) Sebagai Komoditas Unggulan di Kecamatan Tegallalang Kabupaten Badung - PUTRA, I MADE WIYOGA ARIE; SARDIANA, I KETUT; ADI, I GUSTI PUTU RATNA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
Land Suitability Evaluation and Economic Feasibility for the development of Red Ginger Plant (Zingiber offcinale var. Rubrum) as the flagship Commodities in the Subdistrict of Gianyar Regency Tegallalang Development of red ginger plant in Tegalalang District Gianyar regency is one of the gianyar regional government program to make red ginger as a flagship commodity by evaluating the suitability of red ginger plant land in research area and determine economic feasibility. is expected to increase the income of local farmers Tegallalang District Gianyar regency. This research aims to know the characteristics and quality of land Tegallalang District Gianyar Regency, actual and potential land suitability classification, limiting factors and economic feasibility red ginger plants. Comparing between the characteristics/quality of the land with the requirements of growing plants is done to determine the suitability of land in agroecosystem and for economic feasibility is done by calculating the B / C ratio. The sample point is determine by purposive random sampling. The results of this research indicate that the actual land suitability class on V1IAKC land unit is S3na1, V1IIAKC S3eh1.eh2, V1IIIAKC Neh1.eh2, V1IVAKC and V1VAKC Neh1.eh2. The highest economic feasibility of red ginger plant is in unit unit of V1IAKC with B / C ratio of 3.3 and lowest in unit of V1VAKC with B / C ratio is 0.3.